(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2023)
This paper describes earlier studies on the advantages of the incremental sheet forming process. Types of this process are Single-Point Incremental Forming (SPIF), Two-Point Incremental Forming (TPIF), Multi-Point Incremental Forming (MPIF), Double-Sided Incremental Forming (DSIF) and Incremental Sheet Folding with its advantages and applications. It has been shown that the two types of single-point and two-point operations are the most used by researchers, and this depends on the application. These processes are characterized by the fact that they do not require mold or support, so they are considered one of the best processes for manufacturing complex and small parts within a short period of time compared to traditional forming processes. These processes are suitable for different types of materials, including metals, polymers, and ceramics, but not alone, but rather as a composite material with metals. As a literature review some of the process parameters that affected on process output such as, formability, forming force, accuracy and surface roughness were discussed. Final thoughts on the literature found through this review will serve as the researchers' foundation for added investigation.